Preparation of Co-Processed Excipients for Controlled-Release of Drugs Assembled with Solid Lipid Nanoparticles and Direct Compression Materials - Serrano-Mora, Luis Eduardo (Molecules, 2021)
The purpose of the study was to develop a novel, directly compressible, co-processed excipient capable of providing a controlled-release drug system for the pharmaceutical industry. A co-processed powder was formed by adsorption of solid lipid nanoparticles (SLN) as a controlled-release film onto a functional excipient, in this case, dicalcium phosphate dihydrate (DPD), for direct compression (Di-Tab(®)). The co-processed excipient has advantages: easy to implement; solvent-free; industrial scaling-up; good rheological and compressibility properties; and the capability to form an inert platform. Six different batches of Di-Tab(®):SLN weight ratios were prepared (4:0.6, 3:0.6, 2:0.6, 1:0.6, 0.5:0.6, and 0.25:0.6). BCS class III ranitidine hydrochloride was selected as a drug model to evaluate the mixture’s controlled-release capabilities. The co-processed excipients were characterized in terms of powder rheology and dissolution rate. The best Di-Tab(®):SLN ratio proved to be 2:0.6, as it showed high functionality with good flow and compressibility properties (Carr Index = 16 ± 1, Hausner Index = 1.19 ± 0.04). This ratio could control release for up to 8 h, so it fits the ideal profile calculated based on biopharmaceutical data. The compressed systems obtained using this powder mixture behave as a matrix platform in which Fickian diffusion governs the release. The Higuchi model can explain their behavior.